If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 5 = 1 + 3(2x + x) Reorder the terms: 5 + 2x = 1 + 3(2x + x) Combine like terms: 2x + x = 3x 5 + 2x = 1 + 3(3x) Remove parenthesis around (3x) 5 + 2x = 1 + 3 * 3x Multiply 3 * 3 5 + 2x = 1 + 9x Solving 5 + 2x = 1 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 5 + 2x + -9x = 1 + 9x + -9x Combine like terms: 2x + -9x = -7x 5 + -7x = 1 + 9x + -9x Combine like terms: 9x + -9x = 0 5 + -7x = 1 + 0 5 + -7x = 1 Add '-5' to each side of the equation. 5 + -5 + -7x = 1 + -5 Combine like terms: 5 + -5 = 0 0 + -7x = 1 + -5 -7x = 1 + -5 Combine like terms: 1 + -5 = -4 -7x = -4 Divide each side by '-7'. x = 0.5714285714 Simplifying x = 0.5714285714
| 10x-13=6x+2 | | 5j-9=3j+5 | | 3x-2=-23 | | -(6y+2)-(-5y-3)=-6 | | 6+2(x-3)=x-3(1-2x) | | -(6y+2)-(-5-3)=-6 | | 50x^2-8= | | -7x+12=-58 | | 3(4x+1)+2x(1-5x)=2+x | | -2-5g=0 | | 5x+11=-4 | | 11x-5=61 | | 4c-1=2(2c+3) | | 12(2x-4)=3(8x+3) | | 45-4x=4x+15 | | -9x+12=-15 | | 9t-3t= | | 7x^2-16x-20=0 | | 12+6j=24 | | y=x^2+2x-10 | | 8+12t-2=9t+69-4t | | 5n-20=70 | | 128-6x=4x+18 | | 245+-41x+2x^2= | | 245+-42x+2x^2=x | | 55-2x=10+19 | | (x-14)(x-14)+(7-x)(7-x)= | | -4x+3=9 | | 7(y+1)-2=5(y+1)+12 | | 2z+8z=30 | | z-8z= | | 25n-52=148 |